INHIBITORY ACTIVITY OF SNAIL (Achatina fulica (Lam.) Bowdich) MUCUS ON GROWTH OF MAMMARY CANCER IN RAT INDUCED WITH DMBA (7,12-DIMETHYLBENZ(α)ANTHRACENE) - Aan Edison; Phebe Hendra; B. Boy Rahardjo Sidharta; Sri Herwiyanti; Christy Jacub (Sanata Dharma University, 2021)
Back to nature as a medication concept has been accepted widely because it has fewer side effects than modern medicines. Researches on natural products as anticancer agent therapies are in progress. This present research was conducted to determine that the inhibitory activity of snail (Achatina fulica (Lam.) Bowdich) mucus inhibits the growth rate of mammary cancer in SpragueDawley rats. Five groups of female rats, with four individuals each, were induced with 7,12-dimethylbenz(α)anthracene (DMBA) for five weeks. Snail mucus was applied every seven days to the treated rats with three different dosages (15, 20, and 25 mg/kg BW). Observations were done on diameters and growth rate of the mammary cancer lump developed at the end of week 8, 10, 12, 14, and 16. Histopathological examination was carried out at the end of the 16th week. Inhibitory activity results showed a row of average diameter of the cancerous lumps on rats with the following details. The results obtained from the application of snail mucus at dosage of 15, 20, and 25 mg/kg BW were at 0.40, 0.60, and 0.09 cm respectively along with average growth rate of cancerous lumps at 1.50, 0.75, and 0.25. The histopathology results of the snail mucus treatment at dosage of 15, 20, and 25 mg/kg BW showed normal tissue depiction and similarly normal histopathological form indicated by the presence of their sub-clinic components. The results showed that a snail mucus dose of 25 mg/kg BW was able to perform inhibitory activity on growing mammary cancer in rats induced by DMBA.